Prediction of Critical Power and W′ in Hypoxia: Application to Work-Balance Modelling - Townsend, Nathan E.; Nichols, David S.; Skiba, Philip F.; Racinais, Sebastien; Périard, Julien D. (Frontiers in Physiology, 2017)
Purpose: Develop a prediction equation for critical power (CP) and work above CP (W′) in hypoxia for use in the work-balance (W′BAL) model. Methods: Nine trained male cyclists completed cycling time trials (TT; 12, 7 and 3 min) to determine CP and W′ at five altitudes (250, 1250, 2250, 3250 and 4250 m). Least squares regression was used to predict CP and W′ at altitude. A high-intensity intermittent test (HIIT) was performed at 250 and 2250 m. Actual and predicted CP and W′ were used to compute W′ during HIIT using differential (W′BALdiff) and integral (W′BALint) forms of the W′BAL model. Results: CP decreased at altitude (P<0.001) as described by 3rd order polynomial function (R2=0.99). W’ decreased at 4250 m only (P<0.001). A double-linear function characterised the effect of altitude on W′ (R2=0.99). There was no significant effect of parameter input (actual vs predicted CP and W′) on modelled W′BAL at 2250 m (P=0.24). W′BALdiff returned higher values than W′BALint throughout HIIT (P<0.001). During HIIT, W′BALdiff was not different to 0 kJ at completion, at 250 m (0.7±2.0 kJ; P=0.33) and 2250 m (-1.3±3.5 kJ; P=0.30). However, W′BALint was lower than 0 kJ at 250 m (-0.9±1.3 kJ; P=0.058) and 2250 m (-2.8±2.8 kJ; P=0.02). Conclusion: The altitude prediction equations for CP and W′ developed in this study are suitable for use with the W′BAL model in acute hypoxia. This enables the application of W′BAL modelling to training prescription and competition analysis at altitude.